Resquícios do ídiche em Belo Horizonte, Minas Gerais - Laura Silva de Andrade (2022)
This research was carried out within the jewish community in the city of Belo Horizonte, in the state of Minas Gerais, Brazil, with the aim of gathering and analyzing data on the remnants of Yiddish in language commonly used by families of Ashkenazi ascendence. This study carries an important and urgent undertone, as it depends on living speakers of a language currently classified as endangered, with only few speakers in the country. The research was conducted through a series of interviews, followed by sociolinguistic surveys applied to descendents of Ashkenazi jewish families, independently of their self-declared knowledge of the Yiddish language, building from the assumption that the process might trigger knowledge that had been deactivated by the lack of usage while and, at the same time, uncovering lexical items retained in non-Yiddish-speaking generations. This study sheds light into the current scenario of Yiddish language in Belo Horizonte, while threading a registry, so that the memory resonating from the Yiddish language does not disappear due to its ever growing absence in the language of future speakers.